Factors contributing to the promotion of moral competence in nursing. - Keogh, Brian; Mc Cabe, Catherine (My University, 2024)
Ethics is a foundational competency in healthcare inherent in everyday nursing practice. Therefore, the promotion of qualified nurses' and nursing students' moral competence is essential to ensure ethically high-quality and sustainable healthcare. The aim of this integrative literature review is to identify the factors contributing to the promotion of qualified nurses' and nursing students' moral competence. The review has been registered in PROSPERO (CRD42023386947) and reported according to the PRISMA guideline. Focusing on qualified nurses' and nursing students' moral competence, a literature search was undertaken in January 2023 in six scientific databases: CINAHL, Cochrane Library, PsycINFO, PubMed Medline, Scopus and Web of Science. Empirical studies written in English without time limitation were eligible for inclusion. A total of 29 full texts were retrieved and included out of 5233 citations. Quality appraisal was employed using Joanna Briggs Institute checklists and the Mixed Method Appraisal Tool. Data were analysed using inductive content analysis. Research about the factors contributing to the promotion of qualified nurses' and nursing students' moral competence is limited and mainly explored using descriptive research designs. The contributing factors were identified as comprising two main categories: (1) human factors, consisting of four categories: individual, social, managerial and professional factors, and ten sub-categories; and (2) structural factors, consisting of four categories: educational, environmental, organisational and societal factors, and eight sub-categories. This review provides knowledge about the factors contributing to the promotion of qualified nurses' and nursing students' moral competence for the use of researchers, nurse educators, managers, organisations and policymakers. More research about the contributing factors is needed using complex intervention, implementation and multiple methods designs to ensure ethically sustainable healthcare.
PUBLISHED
Keywords: Moral competence; ethical competence; integrative review; nursing; nursing students; qualified nurses